Insurers as Partners in Inclusive Green Growth - Mills, Evan (International Finance Corporation, Washington, DC, 2017)
The Group of 20 (G20) nations increasingly recognize the importance of green growth, and many countries are demonstrating strong leadership through effective and progressive policies. However, governments do not act alone, the private sector is an important partner, providing new technologies, business models and investment opportunities across a variety of sectors to help scale up transformation. In 2012 the G20 Development Working Group commissioned the International Finance Corporation, as the largest development finance institution dedicated to private sector development with a strong emphasis on sustainability, to take stock of mechanisms to mobilize private capital, including from institutional investors, for inclusive green growth investments in developing countries. This work is intended to inform the creation of a public-private G20 Dialogue Platform on Inclusive Green Investment. Insurers can materially engage in green growth in several ways: by helping spread the costs of everyday as well as catastrophic losses (their core business) that so often represent a setback to development efforts; accurately evaluating and communicating risks to inform public and private decision making; offering innovative risk management products and services; providing influential input to the public policy processes; and directly investing some of their substantial assets (more than $20 trillion under management) in inclusive green growth projects and providing risk management tools for other investors.